Leadership Style with Learning Organization - Ramadhan, Dhiva Kumala Putri; Widiarini, Retno (Jurnal Ilmiah Kesehatan (JIKA), 2023)
If an organization improves its organizational learning, of course it will be in line with the increasing performance of its members. Meanwhile, leadership style is the way a leader applies science and art in influencing individuals to achieve organizational goals. This leadership style can have a positive or negative impact on the organization depending on how the leader implements it. Based on data on performance achievements at Puskesmas Tawangrejo Madiun in 2016-2020, performance achievements are unstable. On the other hand, authoritarianism is a very strong leadership style in an organization. The aim of this research was to analyze the relationship between authoritarian leadership style and learning organizations at Puskesmas Tawangrejo Madiun City. This research was quantitative research with a cross sectional approach. The research population consisted of 73 employees of Community Health Center Based on the chi square test results, it was known that the sig value is 0,270>0,05, meaned there was no relationship between authoritarian leadership style and learning organizations. However, a good leadership style and improvement of leader soft skills, communication and self-program development for employees are still needed to achieve common goals.